Nasionalisme Warganegara Indonesia: Tinjauan Kritis terhadap Pasal 2, 3 dan 37 UU No. 20 tahun 2003 tentang SISDIKNAS - Indrawadi, Junaidi (Jurnal Demokrasi, 2008)
This article describes the sense of nationalism of Indonesian citizens nowadays. It is based on several issues of the nation, especially the real condition indicating the decrease of the sense of nationalism. Interethnic group conflict and national disintegration efforts are some of the issues indicated the decrease of the senses. Actually, these issues have been anticipated legally through several regulations, but it seemed that they could not be implemented effectively. At the end of this article I try to offer a solution of the issues through the improvement of civic education learning approach. Kata Kunci: Nasionalisme, disintegrasi bangsa, warganegara, Pendidikan Kewarganegaraan,